The potential of Colocasia esculenta tuber and Zingiber officinale rhizome combined extracts to ameliorate inflammation in monosodium iodoacetate-osteoarthritis rat model - Ni Made Dwi Sandhiutami; Yesi Desmiaty; Yati Sumiyati; Asma Fauziyah Baihaqi; Myra Gracia (Pharmacia, 2023)
This study aims to evaluate effect of Colocasia esculenta and Zingiber officinale combined extract (CEZO) in osteoarthritis rats. Twenty-four Wistar rats were split into normal group, positive group, negative group, and CEZO group on 29th to 43rd day (n = 6). All rats were injected with Na-iodoacetate intraarticularly on first day, unless for the normal group, and then observing the diameter of knee edema until the 28th day (OA rats). On the 43rd day, rats were euthanasia for measurements of hematology, spleen weight, and inflammatory mediators of nitric oxide, matrix metalloproteinase 9, Interleukin-6, and tumor necrosis factor-α using ELISA kit. Our experiments showed that CEZO 90 mg/kgBW was able to decrease knee edema, leukocytes, lymphocytes, spleen enlargement, the concentration of mediators inflammatory NO, TNF-α, IL-6, and protect cartilage degradation by decreased MMP-9 significantly in OA rats. Conclusion of the research is the CEZO 90 mg/kgBW supplementation has potential to be used in osteoarthritis.